Improving Estuarine Flood Risk Knowledge through Documentary Data Using Multiple Correspondence Analysis - Rilo, Ana (2022)
Estuarine margins are usually heavily occupied areas that are commonly affected by compound flooding triggers originating from different sources (e.g., coastal, fluvial, and pluvial). Therefore, estuarine flood management remains a challenge due to the need to combine the distinct dimensions of flood triggers and damages. Past flood data are critical for improve our understanding of flood risks in these areas, while providing the basis for a preliminary flood risk assessment, as required by European Floods Directive. This paper presents a spin-off database of estuarine flood events built upon previously existing databases and a framework for working with qualitative past flood information using multiple correspondence analysis. The methodology is presented, with steps ranging from a spin-off database building process to information extraction techniques, and the statistical method used was further explored through the study of information acquired from the categories and their relation to the dimensions. This work enabled the extraction of the most relevant estuarine flood risk indicators and demonstrates the transversal importance of triggers, since they are of utmost importance for the characterization of estuarine flood risks. The results showed a relation between sets of triggers and damages that are related to estuarine margin land use, demonstrating their ability to inform flood risk management options. This work provides a consistent and coherent approach to use qualitative information on past floods, as a useful contribution in the context of scarce data, where measured and documentary data are not simultaneously available.